2020
DOI: 10.5565/rev/clil.33
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Discourse Functions: A Bridge between Content, Literacy and Language for Teaching and Assessment in CLIL

Abstract: In search of immersion teacher educators' knowledge base: Exploring their readiness to foster an integrated approach to teaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 11 publications
1
31
0
3
Order By: Relevance
“…In the course of the interviews, however, both groups voiced the need for both input and output scaffolding to make historical content accessible to them. Considering that they also mentioned difficulties with expressing certain language functions and responding appropriately to performative verbs, which matches the results by Dalton-Puffer and Bauer-Marschallinger ( 2019), a CDF-based approach appeared to be suitable for the development of CLIL materials, which is in line with suggestions by Morton (2020) and Nashaat Sobhy (2018).…”
Section: Discussion and Implications For The Designsupporting
confidence: 84%
See 1 more Smart Citation
“…In the course of the interviews, however, both groups voiced the need for both input and output scaffolding to make historical content accessible to them. Considering that they also mentioned difficulties with expressing certain language functions and responding appropriately to performative verbs, which matches the results by Dalton-Puffer and Bauer-Marschallinger ( 2019), a CDF-based approach appeared to be suitable for the development of CLIL materials, which is in line with suggestions by Morton (2020) and Nashaat Sobhy (2018).…”
Section: Discussion and Implications For The Designsupporting
confidence: 84%
“…Furthermore, Dalton-Puffer and Bauer-Marschallinger (2019) have shown that the CDF-Construct is compatible with competency-based history education as conceptualized in the Austrian context, both from a theoretical and empirical point of view, indicating that CDFs could work well to operationalize the integration of subject and language learning. Morton (2020), too, argues that CDFs can be used as "building blocks" to foster "focused and principled integration of content, literacy and language" (p. 11). Similarly, Nashaat Sobhy (2018), who looked into the operationalization of teaching definitions in the context of content-based instruction, concludes that Dalton-Puffer's CDF-Construct is "useful in the creation of a blueprint to teaching 'defining'" (p. 108) and recommends to explore CDFs more extensively to "conciliate teaching content and language" (p. 110).…”
Section: Operationalizing the Integration Of Content And Language: Cognitive Discourse Functionsmentioning
confidence: 99%
“…This is evident in the percentage of 55 % of students who have low language skills have low learning outcomes as well. Morton (2020) confirms that there is a relationship between language, content, and literacy. This means that students' language skills are crucial to support the learning outcomes of students.…”
Section: Which Statement Describes What Happens To These Molecules Next?mentioning
confidence: 58%
“…By being motivated, students will be more eager to learn from each other (Namaziandost et al, 2019;Rochman, 2019) and from the teacher (Kukulska-Hulme & Viberg, 2018;Saha & Singh, 2016). As a consequence, the students feel more responsible to actively take part in constructing their knowledge (He & Lin, 2019;Morton, 2020), and strategically learn the target language (Lo & Lin, 2019;Zhong et al, 2019).…”
Section: Discussionmentioning
confidence: 99%